THE EFFECT OF PICTURE WORD INDUCTIVE MODEL (PWIM) ON THE STUDENTS’ ENGLISH WRITING ACHIEVEMENT AT JUNIOR HIGH SCHOOL - Patmawati Aris; Andi Tenri Ampa; Sulfasyah Sulfasyah (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2021)
This research was aimed to know the effect of using Picture Word Inductive Model (PWIM) on the students’ achievement of writing skills.This research implemented the design of quasi-experimental which consisited of two classes of the same level. This research applied total sampling technique, because therewere just two classes of the seventh grade, namely: VII A as the sample of experimental group and VII B as the control group. The total numbers of the sample was 25 students for each group. the data were analyzed quantitatively. The results of statistical analysis showed that the mean score of students' posts in the experimental group was 88.20 which was categorized as “Very Good” while the average post-score of students in the control group was 81.20 which was categorized as “Good”. This shows that after being given treatment, the average value of the experimental group is higher in the control group. It proves that the treatment by applying PWIM can give effect to improve the students’ writing achievement. It was also indicated that t-value (2.78) t-table (1.68), with df. 48, Sig. (2 tailed) and the level of significance was 0.05 which was smaller than t-value (0.008 0.05).This means that there was a significant difference of students’ writing achievement between experimental class and control class after being treated by using PWIM